Comprehensive Review of Health Technology: Innovations in Patient Monitoring, Data Analysis, And Treatment Efficiency - al Jafeesh, Saleh Jafeesh Ghanem; Al Yami, Hamad Hanish Hamad Al Mansour; Alsuliman, Salem Zaid Ali; Al-Marih, Hamad Salem Hussein; Alsaiary, Abdullah Hassan Salem; Aldhaen, Hussain Saeed; Almansour, Yahya Mohammed Hammed; Al Khamsan, Hussain Mohammed; Majrshi, Hashimah Haidar; Al Mawtah, Ali Ibrahim Binali (Journal of Ecohumanism, 2024)
The introduction of health technology into healthcare sectors has transformed the means of monitoring patients, processing information, and administering treatments. Wearable technology and intelligent diagnostic and predictive data analysis have enhanced the quality of care as well as results. Subsequently, this review focuses on identifying and discussing current advances in health technology, their efficiency in practice, patient safety, and overall healthcare organization. Therefore, based on the evaluation of the advantages and drawbacks of the discussed types of technologies, the review aims to offer the audience the idea of their current applicability and perspectives in the healthcare sphere.